Distribution incidence, mortality of tuberculosis and human development index in Iran: estimates from the global burden of disease study 2019 - Hossien Fallahzadeh; Zaher Khazaei; Moslem Lari Najafi; Sajjad Rahimi Pordanjani; Elham Goodarzi (BMC, 2023)
Abstract Background Tuberculosis is one of the most serious challenges facing the global healthcare system. This study aims to investigate the incidence and mortality of tuberculosis in Iran from 2010 to 2019 as well as its relationship with the human development index (HDI). Methods The present study is an ecological study aiming at investigating the incidence and mortality of tuberculosis in Iran during the years 2010 to 2019. The related data were extracted from the Global Burden of Disease (GBD) website. The spatial pattern attributed to tuberculosis in the provinces of Iran was analyzed using ArcGIS software. In this study, the two-variable correlation method was used to analyze the data extracted to study the correlation between Tuberculosis and HDI. Result Based on the results recorded in GBD, the incidence of tuberculosis in 2010, that is, 14.61 (12.72, 16.74), declined compared to 2019, namely 12.29 (10.71, 14.09). The age-standardized mortality rate which was 1.63 (1.52, 1.73) in 2010, has decreased compared to 2019: 1.17 (1.07, 1.32). The incidence and mortality rates of tuberculosis in Iran in all age groups have decreased in 2019 compared to 2010. The highest incidence and mortality among tuberculosis patients were recorded in Sistan and Baluchistan and Golestan provinces. The results indicated that there was a negative and significant correlation between the mortality rate of tuberculosis and the human development index in 2010 (r = -0.509, P-value = 0.003) and 2019 (r = -0.36, P-value = 0.001); however, this correlation between incidence and human development index was not significant (p > 0.05). Conclusion Since mortality is mostly observed in areas with low HDI, health system policymakers must pay more attention to these areas in order to improve care and perform screenings to diagnose and treat patients thus reducing the mortality rate of tuberculosis and preventing an increase in its incidence in Iran.